EUPHEMISMS IN INDONESIAN AND MANDARIN LANGUAGES: A CONTRASTIVE LINGUISTICS ANALYSIS - Ari Kusmiatun; Fu Bo (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
This study describes and compares euphemisms in Indonesian and Mandarin. The research is qualitative and applies a contrastive approach. Data was collected by listening and taking notes and the analysis was conducted by comparative-contrastive description. The results show that there are fourteen realms in comparing Indonesian and Mandarin euphemisms. Further, euphemisms manifest themselves in words, terms, phrases and clauses in these two languages. Euphemisms are used to add politeness and promote harmony in communication – perks of using euphemisms include conflict-mitigation and corroboration of one’s cultural identity. Understanding euphemisms helps foreign students speak better Indonesian in keeping with their own cultural framework.